2011
DOI: 10.1002/chem.201100498
|View full text |Cite
|
Sign up to set email alerts
|

A Multicatalyst System for the One‐Pot Desymmetrization/Oxidation of meso‐1,2‐Alkane Diols

Abstract: Bauen mit Zucker: Glucose fungiert als Reaktionstemplat bei der Synthese des dreidimensionalen, makroporösen Oxids Sm0.2Ce0.8O1.9. Das Material weist eine zweidimensionale Nanoblatt‐Mikrostruktur mit großer Oberfläche auf und hat Potenzial für die Erzeugung gasdichter Membranen mit hoher Ionenleitfähigkeit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…Indeed, by replacing the C-terminal methyl ester group of peptide 273 with a TEMPO-amide functionality they obtained the first member of organic multicatalysts 278 (Boc-L-Pmh-A Gly-L-Cha-L-Phe-NH-TEMPO), bearing two orthogonal catalytic moieties (Scheme 42). 13,112 Remarkably, this proof-of-principle study revealed that the multicatalyst 278 shows an increased oxidation activity compared to TEMPO itself. As a result, the amounts of m-CPBA (3.0 instead of up to 8.0 equivalents) and tetrabutylammonium bromide (5 mol% instead of 30 mol%) could be significantly reduced.…”
Section: Multicatalyst Approachesmentioning
confidence: 77%
“…Indeed, by replacing the C-terminal methyl ester group of peptide 273 with a TEMPO-amide functionality they obtained the first member of organic multicatalysts 278 (Boc-L-Pmh-A Gly-L-Cha-L-Phe-NH-TEMPO), bearing two orthogonal catalytic moieties (Scheme 42). 13,112 Remarkably, this proof-of-principle study revealed that the multicatalyst 278 shows an increased oxidation activity compared to TEMPO itself. As a result, the amounts of m-CPBA (3.0 instead of up to 8.0 equivalents) and tetrabutylammonium bromide (5 mol% instead of 30 mol%) could be significantly reduced.…”
Section: Multicatalyst Approachesmentioning
confidence: 77%
“…7). 103 Additionally, the rate of oxidation was increased using oligopeptide catalyst C-63 compared to the use of free TEMPO. This led to the design of several oligopeptide catalysts containing independent catalyst moieties for both desymmetrisation and oxidation.…”
Section: Acylation Of Diolsmentioning
confidence: 99%
“…The multicatalyst system OC‐21 has been designed to perform one pot desymmetrization/oxidation of meso ‐diols 33. With this catalyst oxidation step occurred under milder conditions than in the separate protocols.…”
Section: Histidine‐based Peptidesmentioning
confidence: 99%
“…[32] The multicatalyst system OC-21 has been designed to perform one pot desymmetrization/oxidation of meso-diols. [33] With this catalyst oxidation step occurred under milder conditions than in the separate protocols. Under optimized reaction conditions yields and selectivities in desymmetrization of several meso-diols are generally good (Scheme 21).…”
Section: Histidine-based Peptidesmentioning
confidence: 99%